2020
DOI: 10.1002/ijc.32839
|View full text |Cite
|
Sign up to set email alerts
|

The second round of the Dutch colorectal cancer screening program: Impact of an increased fecal immunochemical test cut‐off level on yield of screening

Abstract: The Dutch colorectal cancer (CRC) screening program started in 2014, inviting the target population biennially to perform a fecal immunochemical test (FIT). We obtained prospectively collected data from the national screening information‐system to present the results of the second round (2016) and evaluate the impact of increasing the FIT cut‐off halfway through the first round from 15 to 47 μg Hb/g feces on outcomes in the second round. Second round screening was done with a 47 μg Hb/g feces FIT cut‐off. Part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 18 publications
1
24
0
Order By: Relevance
“…In the third scenario, we accounted for suboptimal adherence to diagnostic and surveillance colonoscopy and for decreasing adherence over multiple screening rounds ( 36 ). For this scenario, we assumed a 100% adherence at the first screening and that 90% of the people screened at a given age would participate again at the next recommended age ( 37 , 38 ). In line with current CRC participation rates ( 39 ), we assumed screening adherence would not drop below 60% at any age by assuming that 15% of the people who previously did not participate would participate at the next recommended age.…”
Section: Methodsmentioning
confidence: 99%
“…In the third scenario, we accounted for suboptimal adherence to diagnostic and surveillance colonoscopy and for decreasing adherence over multiple screening rounds ( 36 ). For this scenario, we assumed a 100% adherence at the first screening and that 90% of the people screened at a given age would participate again at the next recommended age ( 37 , 38 ). In line with current CRC participation rates ( 39 ), we assumed screening adherence would not drop below 60% at any age by assuming that 15% of the people who previously did not participate would participate at the next recommended age.…”
Section: Methodsmentioning
confidence: 99%
“…A recent health economic modeling study revealed that adding an annual universal cancer screening test to the current standard of care in human medicine would reduce late-stage cancer incidence by 78% in those intercepted by the screening test, and result in an absolute reduction of 26% in all cancer deaths ( 227 ). The practice of screening at regular intervals relies on the concept of “cumulative detection” to improve the clinical sensitivity over time at the population level, as sequential testing holds the benefit of detecting cases missed on initial screening ( 108 , 109 , 228 ). Ultimately, this technology may support cancer screening in lower-risk canine populations as well, comparable to how NIPT technology expanded beyond high-risk cases to encompass all pregnancies in humans ( 229 ).…”
Section: Liquid Biopsy: the Next Frontier In Veterinary Cancer Carementioning
confidence: 99%
“…colonoscopies in CRC screening programs (4,19). However, this option is not always followed in countries that use FIT as the screening test, because it implies that lesions with insufficient bleeding might not test positive, and thus, would be missed.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have evaluated the impact of raising the FIT cut-off point to match the demand to the availability of colonoscopies in CRC screening programs ( 4 , 19 ). However, this option is not always followed in countries that use FIT as the screening test, because it implies that lesions with insufficient bleeding might not test positive, and thus, would be missed.…”
Section: Discussionmentioning
confidence: 99%